Bovine serum albumin nanoparticles improve the antitumour activity of curcumin in a murine melanoma model. (4th July 2018) - Camargo, Luciana Erzinger Alves de; Brustolin Ludwig, Daniel; Tominaga, Tania Toyomi; Carletto, Bruna; Favero, Giovani Marino; Mainardes, Rubiana Mara; Khalil, Najeh Maissar
Abstract: Curcumin is a natural compound presenting important antitumour activity. However, due to its low aqueous solubility, instability at physiological pH, and low oral bioavailability, its clinical use is limited. Bovine serum albumin (BSA) nanoparticles have been used as drug carriers to improve the drug properties. In this work, curcumin-loaded BSA nanoparticles were developed and the in vitro cytotoxicity over murine melanoma cells and the in vivo antitumour activity in a murine melanoma model were assessed. Nanoparticles presented 150 nm, polydispersity index of 0.16, negative zeta potential, and 45% of curcumin encapsulation efficiency. Curcumin release from nanoparticles was slow and diffusion dependent. In the cytotoxicity assay, free curcumin was more efficient than curcumin-loaded nanoparticles, probably due to the prolonged curcumin release from nanoparticles. However, in a murine melanoma model, curcumin-loaded nanoparticles presented higher antitumour efficiency than free curcumin. BSA nanoparticles are efficient curcumin carriers that may have relevant applications in melanoma treatment.